TOOL OR TOY: A SURVEY OF PARENTAL ATTITUDES TOWARDS THE USE OF CELL PHONES AT SCHOOLS IN ZIMBABWE - Manyarara, Barbara C (Commonwealth Youth and Development, 2017)
The paper surveys parental attitudes to secondary school students’ use of cellphones in Zimbabwe after a ministerial pronouncement caused a media storm that even parliament failed to resolve, especially since parents as stakeholders had not been consulted on what could become policy. The current paper sought to fill this information gap by briefly surveying parental attitudes and motivations for accepting or rejecting the use of cell phones at school by adolescents. A descriptive survey research design was used and the researcher accessed her research population through the WhatsApp application of her smartphone. The interactive nature of the WhatsApp messaging platform merged several forms of data gathering and resulted in semi-questionnaires, minor document analysis, and a loosely scripted interview. Feedback and clarifications between the researcher and respondents were almost immediate. The data were subjected to both qualitative and quantitative analyses and showed that the majority of parents do not want adolescents to take cell phones to school for various reasons. The most serious were: distracting learners because they are addictive; promoting pornography; and cyber-bullying. A few believed cell phones were useful in emergencies; and can enhance learning. Short of ministerial imposition, parents have rejected the use of cell phones at school by adolescents.